Enterprise 2.0 post-adoption: Extending the information system continuance model based on the technology-Organization-environment framework. (February 2017) - Jia, Qiong; Guo, Yue; Barnes, Stuart J.
Abstract: This paper extends the IS continuance model to improve our understanding of the determinants of E2.0 post-adoption. Our proposed research model incorporates four constructs into the IS continuance model: firm size, firm scope, subjective norms and competitive pressure from the perspective of organizational and environmental context based on the TOE framework. Results from a survey of customers of Mingdao, a leading Enterprise 2.0 platform in China, support our model. The research findings show that organizational and environmental context factors, including subjective norms and competitive pressure, significantly influence enterprises' intentions to renew their E2.0 service in addition to technology perceptions. Perceived usefulness and satisfaction are no longer the strongest predicators of continuance usage in the context of enterprise systems. The theoretical and managerial implications of these results are discussed. Highlights: An empirical study of E2.0 post-adoption based on real firm users. Integrating firm-level factors based on the TOE framework. Extending the IS Continuance Model to the firm adoption context.